Medical navigation based on coloured markers for image-guided surgery - Elsamnah, Fahed; Sediono, Wahju (Elsevier Ltd., 2014)
Image-guided Surgery (IGS) is an advanced medical navigation technology that enhances surgical operations and outcomes. The infrared markers have been used in previous years as references to visualize a patient's body part, whether the markers are active or passive. This paper presents a new reference tool of tracking, and develops a new algorithm of tracking an object in real time. Three coloured markers have been used as references of visualizing a patient's body part by providing many advantages, such as an unbounded objects tracking, an inexpensive system compared to the IR-markers system, and an unrestricted working area. This paper shows that using a coloured marker as a reference, a good accuracy of visualization (RMS error 3.78 mm) at the distance of 1000 to 1300 mm can be generated. Image filtering techniques have been used to process the images captured from a stereo camera. As a result, medical navigation based on coloured markers contributes a promising result of Image-Guided Surgery. Moreover, a faster algorithm for a real time tracking of coloured markers has been developed.